THE USE OF THERAPEUTIC AND PROPHYLACTIC COMPLEX IN ORTHOPEDIC PATIENTS USING ADHESIVE MEANS TO IMPROVE THE MICROBIOLOGICAL STATUS OF THE ORAL CAVITY - Verbovska, R.I. (World of Medicine and Biology, 2019)
The need for orthopedic treatment for complete removable dentures in the age group 50 years and older ranges from 23.8% to 80%. One of the factors that influence changes in the microbiological status of the oral cavity is the use of removable plate prostheses, the use for better fixation of their adhesive agents, which negatively affect the microbiocenosis of the oral cavity. Patients were offered a treatment-and-prophylactic complex for the prevention and treatment of complications from the use of complete removable plate prostheses using adhesive agents. The results of the proposed treatment in all study groups show a positive dynamics and a tendency to increase the degree of colonization of representatives of the resident microflora of the mouth in patients with complete absence of teeth after treatment.